Ammonia as a Potential Neurotoxic Factor in Alzheimer's Disease - Adlimoghaddam, Aida; Sabbir, Mohammad G.; Albensi, Benedict C. (Frontiers in Molecular Neuroscience, 2016)
Ammonia is known to be a potent neurotoxin that causes severe negative effects on the central nervous system. Excessive ammonia levels have been detected in the brain of patients with neurological disorders such as Alzheimer disease (AD). Therefore, ammonia could be a factor contributing to the progression of AD. In this review, we provide an introduction to the toxicity of ammonia and putative ammonia transport proteins. We also hypothesize how ammonia may be linked to AD. Additionally, we discuss the evidence that support the hypothesis that ammonia is a key factor contributing to AD progression. Lastly, we summarize the old and new experimental evidence that focuses on energy metabolism, mitochondrial function, inflammatory responses, excitatory glutamatergic and GABAergic neurotransmission, and memory in support of our ammonia-related hypotheses of AD.